Aicapexp: a diagnostic toolkit for enhancing ai readiness in libraries - Masrek, Mohamad Noorman; Baharuddin, Mohammad Fazli; Mohamed Shuhidan, Shamila; Mohamad Rosman, Mohamad Rahimi (2025)
The AI Capability Explorer (AICAPEXP) is a comprehensive diagnostic toolkit designed to help libraries assess, benchmark, and enhance their artificial intelligence (AI) capabilities. Built upon extensive research into AI integration within library environments, this toolkit offers a structured framework to evaluate readiness across multiple dimensions including infrastructure, human resource competencies, data governance, ethical safeguards, and user engagement. AICAPEXP is particularly useful for library leaders, digital transformation officers, and policy makers seeking to align their services with emerging AI-driven innovations. It empowers institutions to identify existing gaps, set strategic priorities, and track progress over time, thereby fostering a culture of continuous improvement and future-readiness. The development of AICAPEXP is grounded in scholarly and empirical insights, incorporating international best practices, stakeholder feedback, and validated indicators of AI maturity in knowledge-centric organisations. Its modular and adaptable design ensures relevance to libraries of various sizes and contexts—public, academic, research, and special libraries alike. With growing global demand for responsible and effective AI adoption, AICAPEXP holds strong commercial potential. It can be packaged as a professional service, consultancy offering, or licensing solution for institutions seeking expert support in AI-readiness planning. Moreover, its evidence-based structure offers credibility and value for accreditation bodies and funding agencies evaluating digital innovation capacity. Whether your library is just beginning its AI journey or seeking to strengthen existing initiatives, AICAPEXP serves as both a strategic compass and an operational guide for sustainable AI integration in library services.